Literature Review and Bibliometric Mapping Analysis: Philosophy of Science and Technology Education - Dwi Fitria Al Husaeni; M. Munir (Universitas Pendidikan Indonesia (UPI), 2023)
The research objective is to conduct a literature review regarding the philosophy of science views on science and technology, especially in the field of Education. Bibliometric analysis was carried out through mapping visualization using VOSviewer. The research method is Systematic Literature Review (SLR). Bibliometric analysis mapping has 4 stages: data search, data processing, data mapping, and data analysis. The keywords used are